Cochlear implant electrode impedance subcomponents as biomarker for residual hearing - Schraivogel, Stephan; Aebischer, Philipp; Weder, Stefan; Caversaccio, Marco; Wimmer, Wilhelm (Frontiers in Neurology, 2023)
Introduction and objectives Maintaining the structural integrity of the cochlea and preserving residual hearing is crucial for patients, especially for those for whom electric acoustic stimulation is intended. Impedances could reflect trauma due to electrode array insertion and therefore could serve as a biomarker for residual hearing. The aim of this study is to evaluate the association between residual hearing and estimated impedance subcomponents in a known collective from an exploratory study. Methods A total of 42 patients with lateral wall electrode arrays from the same manufacturer were included in the study. For each patient, we used data from audiological measurements to compute residual hearing, impedance telemetry recordings to estimate near and far-field impedances using an approximation model, and computed tomography scans to extract anatomical information about the cochlea. We assessed the association between residual hearing and impedance subcomponent data using linear mixed-effects models. Results The progression of impedance subcomponents showed that far-field impedance was stable over time compared to near-field impedance. Low-frequency residual hearing demonstrated the progressive nature of hearing loss, with 48% of patients showing full or partial hearing preservation after 6 months of follow-up. Analysis revealed a statistically significant negative effect of near-field impedance on residual hearing (−3.81 dB HL per kΩ; p < 0.001). No significant effect of far-field impedance was found. Conclusion Our findings suggest that near-field impedance offers higher specificity for residual hearing monitoring, while far-field impedance was not significantly associated with residual hearing. These results highlight the potential of impedance subcomponents as objective biomarkers for outcome monitoring in cochlear implantation.